Critique of the power of judgment - Kant, Immanuel, 1724-1804.; Guyer, Paul, 1948- (Cambridge, UK ; New York : Cambridge University Press, 2000)
"This entirely new translation of Kant's masterpiece follows the principles and high standards of all other volumes in The Cambridge Edition of the Works of Immanuel Kant with extensive annotation, glossaries, and an index. This volume includes the indispensable first draft of Kant's introduction to the work. It is the only English edition to note the many differences between the first (1790) and second (1793) editions of the work, and among the copious citations and sources are references to the relevant passages on aesthetics in Kant's lectures on anthropology recently published for the first time in German." "All in all, this new edition offers the serious student of Kant a richer, more complete, and more accurate translation than has ever been available in English."--Jacket.
Editor's introduction -- First introduction to the Critique of the Power of Judgment -- Critique of the Power of Judgement -- Preface -- Introduction -- First part: critique of the aesthetic power of judgment -- First section, first book: analytic of the beautiful -- First section, second book: analytic of the sublime -- Deduction of pure aesthetic judgments -- Second section: the dialectic of the aesthetic power of judgment -- Appendix: on the methodology of taste -- Second part: critique of the teleological power of judgment -- First division: analytic of the teleological power of judgment -- Second division: dialectic of the teleological power of judgment -- Appendix: methodology of the teleological power of judgment.
Includes bibliographical references (p. xlix-lii) and index.
Translated from the German.
Keywords: Judgment (Logic) -- Early works to 1800.; Judgment (Aesthetics) -- Early works to 1800.; Aesthetics -- Early works to 1800.; Teleology -- Early works to 1800.